Nab-paclitaxel/gemcitabine combination is more effective than gemcitabine alone in locally advanced, unresectable pancreatic cancer – A GISCAD phase II randomized trial. (May 2021) - Cascinu, Stefano; Berardi, Rossana; Bianco, Roberto; Bilancia, Domenico; Zaniboni, Alberto; Ferrari, Daris; Mosconi, Stefania; Spallanzani, Andrea; Cavanna, Luigi; Leo, Silvana; Negri, Francesca; Beretta, Giordano D.; et al.
Abstract: Background: The role of combination chemotherapy has not yet been established in unresectable locally advanced pancreatic cancer (LAPC) lacking dedicated randomized trials. Methods: This phase II trial tested the efficacy of Nab-paclitaxel (NAB-P)/Gemcitabine (G) versus G alone. Patients were randomized, 1:1 to G 1000 mg/m 2 on days 1, 8 and 15 every 28 days versus NAB-P 125 mg/m 2 on days 1, 8 and 15 every 28 days plus G 1000 mg/m 2 on days 1, 8 and 15 every 28 days. Disease progression rate after three cycles of chemotherapy was the primary end-point. Progression-free survival (PFS), overall survival (OS) and response rate were secondary end-points. Findings: A total of124 patients were enrolled. The study showed a reduction of a progressive disease from 45.6% with G to 25.4% with NAB-P/G (P = 0.01) at 3 months. Noteworthy, at 6 months in the G arm, 35.6% of patients present a metastatic spread versus 20.8% in the NAB/G arm. The response rate was 5.3% in the G arm and 27% in the NAB/G arm. Median PFS was 4 months for the G arm and 7 months for the NAB-P/G arm. Median OS was 10.6 in the G arm and 12.7 months in the NAB-P/G arm. One patient died during treatment with G due to a stroke. Interpretation: NAB-P/G reduced the rate of LAPC patients progressing after three cycles of chemotherapy compared with G, especially in terms of distant relapses. It positively affects PFS. To the best of our knowledge, this is the first randomized trial providing evidence that combination chemotherapy is superior to gemcitabine alone in this setting. ClinicalTrials.gov Identifier: NCT02043730 . Highlights: Role of combination chemotherapy has not been demonstrated in locally advanced PDAC. Nab-paclitaxel/gemcitabine combination improved PFS, OS and RR in these patients. Combination chemotherapy delays the onset of a metastatic disease in these patients.